STEM-Based Professional Development Model to Improve Teachers' Perceptions and Students' STEM Literacy: A Mixed Research Approach - Ardianto, Didit; Windiyani, Tustiyana; Puteri, Anisa; Aziz, Helmi; Suwarma, Irma Rahma; Yunus, Sitti Rahma (Jurnal Pendidikan IPA Indonesia, 2026)
This study examines the effect of a structured professional development model on enhancing primary teachers' understanding and their capacity to promote students' STEM literacy. A mixed-methods design was employed to capture both quantitative outcomes and qualitative insights. Pre-test and post-test intervention surveys were used to measure shifts in teachers' perceptions, while students' literacy was assessed through structured essay tasks. Complementing this, open-ended questionnaires and interviews with selected teachers and students were conducted to explore their experiences and the perceived impact of the programme. The results demonstrate significant improvements in teachers' perceptions of STEM education and students' STEM literacy following the program's implementation. Quantitative findings indicate a substantial increase in teachers' self-efficacy and confidence in implementing STEM-based instruction, accompanied by measurable gains in students' STEM literacy across participating schools. These improvements are further explained and supported by qualitative findings, which reveal that teachers perceived the program as effective in strengthening their STEM content knowledge, pedagogical competence, and instructional confidence through hands-on learning activities, collaborative practices, and sustained professional support. In addition, qualitative evidence highlights contextual challenges, including limited instructional time and insufficient resources, which help explain variations in implementation effectiveness among schools. Overall, the findings suggest that a well-designed, contextually responsive STEM professional development model can enhance teacher capacity and meaningfully improve student STEM literacy in primary education, while underscoring the importance of ongoing support for sustainable implementation.